Pesantren Salaf dan Respons Perubahan: Potret Pengembangan Pondok Pesantren Annur Azzubaidi, Konawe - Sabdah Sabdah; Sastramayani Sastramayani (Institut Agama Islam Negeri (IAIN) Kendari, 2020)
Although pesantren have proven themselves to be one of the suppliers of human resources in Indonesia, the challenges are now more complex. Competition between Islamic educational institutions, or even with public labeled education should be one of the concerns of the managers of the cottage, so that its relevance to development is maintained. Through a qualitative approach, this article presents search results at the Annur Azzubaidi Pesantren, a traditional pesantren (salaf) in Konawe. The view that educational institutions must now prepare themselves in a competitive climate, apparently for pesantren this is not the case. The leadership considers that the intention of competition can divert the initial spirit of the establishment of pesantren as a means of devotion to the creator. Competition is worldly temptations that can disrupt the sacred intentions in educating noble-minded generations. The response of this institution by accommodating the modern education system in the form of madrasas is only a form of understanding the needs of students. Conservatism in the sense of maintaining the pesantren tradition is still very strong in the Annur Azzubaidi Islamic Boarding School. Keywords: Competition, Change, Salaf Boarding School